2021
DOI: 10.47028/j.risenologi.2021.61.156
|View full text |Cite
|
Sign up to set email alerts
|

Online Lectures Using Zoom Application For Undergraduate Students During Covid-19 Pandemic Period

Abstract: This research aimed to obtain information about online learning using the Zoom application for the PGSD students of FKIP of Widya Gama Mahakam University of Samarinda during the Covid-19 pandemic. This research used a qualitative descriptive approach. This research subjects were PGSD students who actively participated in online lectures and selected nine sources, namely four students of class 2018 and five students of class 2019. The selection of these sources used a purposive sampling method. Data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…According to Oktaviani (2021), Zoom has some limitations and challenges. Handling Zoom might be difficult at the initial stages like other applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Oktaviani (2021), Zoom has some limitations and challenges. Handling Zoom might be difficult at the initial stages like other applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mamtani et al (2021) highlight that several technical and connectivity issues impact learner anxiety. Oktaviani (2021) reported that the Zoom application is sometimes unable to support online lectures due to an unstable network, so its access is automatically disconnected. Insufficient storage capacity on mobile phones to install Zoom, poor internet connectivity due to the student's home's remote area, and undesirable weather are supplemental barriers.…”
Section: Suggest Writing Instructions In the Chat Box As Well When De...mentioning
confidence: 99%
“…This application is equipped with various features such as video, microphone, room chat, raise hand, applause, etc. Siska Oktaviani (2021) argues that the Zoom application can be used on laptop and smartphone for free with a maximum capacity of 100 participants with a time limit to 40 minutes and no time limit with paid Zoom application. So, Zoom application is widely used as a learning media when online learning because this application can be operated via laptop or smartphone and the participant capacity is large.…”
Section: Introductionmentioning
confidence: 99%